Wild School - Mackinnon, Mairi; Lee Wildish (London Usborne Publishing, 2010)
The eleventh title in the new "Usborne Very First Reading" series, designed for younger children to introduce them to reading together with their parents. Parents and children take turns to read from the page (the text clearly marked for who should be reading) and as the books progress in the series the adults read less and the child more.
Includes Color Illustrations
Keywords: Stories in rhymes -- School